Effect of graphene, silicon, and silver doping on the mechanical and structural properties of advanced epoxy composites - Abdulnabi, Duha M.; adhel, A.F. Essa, Abbas F (Edelweiss Applied Science and Technology, 2025)
In this study, the effect of incorporating graphene, silicon, and silver nanoparticles into epoxy composites was investigated to enhance their mechanical and structural properties. The research examined various combinations of these materials, including pure epoxy, epoxy/graphene (0.1 wt.%), epoxy/graphene/Si/Ag (0.1-1 wt.%), and epoxy/Si/Ag (0.1-1 wt.%) composites. The structural characteristics were analyzed using XRD and FE-SEM techniques, while mechanical properties were evaluated through tensile testing. Results showed that the addition of graphene significantly improved the crystallinity and structural organization of the composites. The optimal results were achieved in the ternary system (epoxy/graphene/Si/Ag) with 1 wt.% Si +Ag content, showing an enhanced elastic modulus of 0.30 kN/mm² compared to pure epoxy (0.23 kN/mm²). FE-SEM analysis revealed that graphene helped create a uniform network structure that effectively distributed the Si and Ag particles throughout the matrix, leading to improved mechanical performance.